Melampyrum Cristatum L. – A Rare River Corridor Plant in Wielkopolska and Poland - Stachnowicz, Wojciech (Biodiversity: Research and Conservation, 2015)
Melampyrum cristatum is an extremely rare, native, hemi-parasitic, vascular plant, recently considered to be extinct in Poland. The article presents data concerning new localities of the species recorded in 2007-2012 in the valley of the River Warta (Wielkopolska, Poland). Local distribution of M. cristatum in the Natura 2000 sites: PLH300012 - Rogalińska Dolina Warty (ca. 147.5 sq. km) and PLH300053 - Lasy Żerkowsko-Czeszewskie (ca. 71.6 sq. km), as well as its updated regional (in Wielkopolska) and national (Poland) ranges are shown on maps and interpreted on the background of the geomorphic diversity of occupied habitats. The results suggest that in Poland the species is distributed mainly along valleys of large, lowland rivers, which corresponds with its ‘River Corridor Plant’ status in Central Europe. The species rarity is discussed considering its outline phytocoenological scale (comprising various plant communities within 6 syntaxonomical classes), the riverine distribution pattern and chosen biological features. Natural habitat heterogeneity along with changeable water regime in floodplains, as well as potential limitations of myrmecochoric seed dispersal, may constitute potential reasons for the species low frequency